Significant decrease of mortality due to anastomotic leaks following esophageal resection: management makes the difference - Schaible, Anja; Brenner, Thorsten; Hinz, Ulf; Schmidt, Thomas; Weigand, Markus A.; Sauer, Peter; Büchler, Markus W.; Ulrich, Alexis (Langenbeck's archives of surgery, 2017)
Purpose: Anastomotic leakage is the most frequent cause of postoperative mortality following esophageal surgery. However, no gold standard for diagnosing and managing leakage has been established. Continuous clinical judgment is extremely important; therefore, to optimize the management of leakage, we established a special group for decision-making in cases of suspected leakage in the early postoperative period. Methods: Between January 2010 and December 2016, 234 consecutive patients underwent elective esophageal resection with a thoracoabdominal incision. In 2014, we established a group consisting of a surgeon, surgical endoscopist, and anesthesiologist for decision-making in cases of suspected leakage. They discussed emerging problems and decided on further diagnostics or therapy. The data were documented prospectively and compared to the years prior to 2014. Results: Two hundred and thirty-four consecutive patients were enrolled in the study, 110 in the years 2010–2013 (group A), and 124 in the years 2014–2016 (group B). Neither patients’ characteristics nor the rate of anastomotic leakage differed significantly between the two study groups. The hospital mortality rate was 10% (11 patients) in group A and 4.8% (six patients) in group B. Most interestingly, mortality due to anastomotic leakage was 35% in group A (9/26), whereas it decreased significantly to 6.5% (2/31 patients) (P < 0.001) in group B. Conclusions: Our data clearly demonstrated that optimizing the management of anastomotic leakage by making team decisions can lead to a significant decrease in mortality.
Gesehen am 09.04.2018